Late Onset Diaphragmatic Hernia: A Forgotten Etiology of Recurrent Vomiting in the Adolescent Population - Kwag KH; Habibi Zoham M; Brown B; Sohn A; Harrison S; Brandwein A (Dove Medical Press, 2023)
Koren Hyogene Kwag,1 Mojdeh Habibi Zoham,1 Brande Brown,1 Andy Sohn,2 Sebron Harrison,3 Ariel Brandwein1 1Department of Pediatrics, New York-Presbyterian Brooklyn Methodist Hospital, Brooklyn, NY, USA; 2Department of Surgery, New York-Presbyterian Brooklyn Methodist Hospital, Brooklyn, NY, USA; 3Department of Cardiothoracic Surgery, Weill Cornell Medicine, New York, NY, USACorrespondence: Koren Hyogene Kwag, Department of Pediatrics, New York-Presbyterian Brooklyn Methodist Hospital, 506 6th Street, Brooklyn, NY, 11215, USA, Tel +1 718 780-5970, Fax +1 718 780-3266, Email khk7006@nyp.orgAbstract: Diaphragmatic hernia is a rare disorder in adolescents with oftentimes delayed diagnosis due to late-onset and non-specific clinical manifestations. In this report, we present a case of diaphragmatic hernia in an 18-year-old male, where initial diagnosis was complicated by confounding factors of type 1 diabetes mellitus and cannabinoid hyperemesis syndrome. This case highlights the importance of having a high index of suspicion for diaphragmatic hernia in patients with nonspecific gastrointestinal symptoms to ensure timely recognition and surgical intervention.Keywords: diaphragmatic hernia, Bochdalek hernia, Morgagni hernia, type 1 diabetes mellitus, cannabinoid hyperemesis syndrome, vomiting, gastrointestinal symptoms